EFA6 regulates selective polarised transport and axon regeneration from the axon initial segment - Eva, Richard; Koseki, Hiroaki; Kanamarlapudi, Venkateswarlu; Fawcett, James W (Journal of cell science, 2017)
Central nervous system (CNS) axons lose their intrinsic ability to regenerate upon maturity, whereas peripheral nervous system (PNS) axons do not. A key difference between these neuronal types is their ability to transport integrins into axons. Integrins can mediate PNS regeneration, but are excluded from adult CNS axons along with their Rab11 carriers. We reasoned that exclusion of the contents of Rab11 vesicles including integrins might contribute to the intrinsic inability of CNS neurons to regenerate, and investigated this by performing laser axotomy. We identify a novel regulator of selective axon transport and regeneration, the ARF6 guanine-nucleotide-exchange factor (GEF) EFA6 (also known as PSD). EFA6 exerts its effects from a location within the axon initial segment (AIS). EFA6 does not localise at the AIS in dorsal root ganglion (DRG) axons, and in these neurons, ARF6 activation is counteracted by an ARF GTPase-activating protein (GAP), which is absent from the CNS, ACAP1. Depleting EFA6 from cortical neurons permits endosomal integrin transport and enhances regeneration, whereas overexpressing EFA6 prevents DRG regeneration. Our results demonstrate that ARF6 is an intrinsic regulator of regenerative capacity, implicating EFA6 as a focal molecule linking the AIS, signalling and transport.This article has an associated First Person interview with the first author of the paper.
Keywords: Animals; rab proteiny vázající GTP; amyloidový prekurzorový protein beta; primární buněčná kultura; GTPase-Activating Proteins; mikrotubuly; alfa řetězce integrinu; Embryo, Mammalian; Gene Expression Regulation, Developmental; iniciální segment axonu; proteiny aktivující GTPasu; výměnné faktory guaninnukleotidů; Dendrites; dendrity; Guanine Nucleotide Exchange Factors; malá interferující RNA; neurony; signální transdukce; Signal Transduction; Axon Initial Segment; Rats, Sprague-Dawley; Neurons; Integrin alpha Chains; Male; potkani Sprague-Dawley; Ganglia, Spinal; RNA, Small Interfering; spinální ganglia; krysa rodu Rattus; mozková kůra; Amyloid beta-Protein Precursor; Axonal Transport; Cerebral Cortex; Microtubules; zvířata; mužské pohlaví; rab GTP-Binding Proteins; vývojová regulace genové exprese; axonální transport; embryo savčí; Rats; Primary Cell Culture